Tem mulher na macumba “sim sinhô”: as mulheres negras na macumba religiosa e musical carioca entre 1870 e 1930 - Rivas, Maria Elise Gabriele Baggio Machado (2017)
This paper adresses black women in the macumbas of Rio de Janeiro, in the newspapers of such city, from 1870 to 1930, aiming to analyse their presence or absence in the macumbas. There are two hypothesis here considered: to verify if the presence of black women found in the researched material (that is, the newspapers of Rio de Janeiro) equals their importance in the macumbas, and to verify how much do the papers performed by man and women in the terreiros influence or not the musical macumba regarding aesthetics. The research uses a feminist perspective, so the theoretical reference privileges gender. I recollect Fiorenza’s hermeneutics of suspicion (1992) in order to find women in the newspaper, a historical look that aims to find them as characters of day by day in Perrot (2005), and a anthropologic approach of black women in the Candomblés in Bernardo (2005-2005). Also, we refer to Pollak (1989) and the underground memory, and to Weber (2013) and the separation of the issues in order to understand better the division of macumba into religious and musical. The empirical field is formed by 19 newspapers that were active in the city of Rio de Janeiro through the chosen period. Such newspapers are available in the Hemeroteca Digital of Rio de Janeiro, so the analyzed material is a primary source. Methodology used to analyze the newspapers is the approach given by Zicman (1985). It is worth mentioning that too much effort has been needed so we could find black women in both macumbas: they were there